2011
DOI: 10.1111/j.1440-1754.2011.02016.x
|View full text |Cite
|
Sign up to set email alerts
|

Staff immunisation: Policy and practice in child care

Abstract: The level of awareness of specific staff immunisation recommendations was relatively low. The transition of knowledge to policy was encouraging, although implementation of policies requires further commitment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…Only 6% of centres mentioned the “Staying Healthy in Child Care” manual. A previous study is Australia in 2006 also identified low awareness of guidelines for staff immunisation [20]. In the four years since this study, the implementation of these guidelines has not changed and remains low.…”
Section: Discussionmentioning
confidence: 79%
“…Only 6% of centres mentioned the “Staying Healthy in Child Care” manual. A previous study is Australia in 2006 also identified low awareness of guidelines for staff immunisation [20]. In the four years since this study, the implementation of these guidelines has not changed and remains low.…”
Section: Discussionmentioning
confidence: 79%
“…Apart from the data presented in this study, there have been few previous attempts to document vaccine uptake in the childcare sector. One study conducted by Spokes et.al over 10 years ago, involved a survey of New South Wales based childcare directors ( n = 437) to determine their level of knowledge towards the NHMRC recommendations for the immunisation of child-care workers and to ascertain whether the knowledge had translated into practices [12]. The study found that only 49% of the respondents were aware of the policy and just over half had a staff immunisation policy in place.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, when tracking the course of a bill through Congress, it is convenient to specify the "HR" or "S" number. 3 Both HR and S require approval by the other body and the signature of the president to become law.…”
Section: Key Legislation In Biosecurity (Or How Congressional Intent mentioning
confidence: 99%
“…"Biosecurity" takes on an entirely different meaning in international political agreements such as the Biological and Toxin Weapons Convention of 1975, where it refers to measures to prevent the research and development of microorganisms or their products for hostile purposes [2]. And it is not too far a reach to think of biosecurity as the prevention of infectious disease -and specifically communicable infectious disease -in humans [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation